Case Report: Retroaortic Innominate Vein With Supracardiac Total Anomalous Pulmonary Venous Connection - Ifuku, Toshinobu; Kuraoka, Ayako; Ohhira, Tomoko; Sagawa, Koichi; Nakano, Toshihide; Kado, Hideaki (Frontiers in Pediatrics, 2021)
A retroaortic innominate vein (RAIV) is a rare anomaly that passes posterior to the ascending aorta to join the superior vena cava and is associated with congenital heart disease (CHD). The RAIV and normal left innominate vein (LIV) rarely duplicate. The etiology of the RAIV and its relationship with CHD remains unknown. We report a case involving a 1-month-old baby girl with RAIV and supracardiac total anomalous pulmonary venous connection (TAPVC). Transthoracic echocardiogram demonstrated a pulmonary venous confluence (CPV) posterior to the left atrium, an abnormal vertical vein (VV) that originated from the CPV, and a normally positioned LIV. Three-dimensional cardiac computed tomography revealed the VV and RAIV to which it merged. This is the first reported case of a combination of RAIV and isolated TAPVC. We speculate that the VV is connected to the CPV during fetal life, thus leaving the RAIV behind. The RAIV may be detected in various forms with the development of new diagnostic imaging methods. Although a RAIV itself does not require treatment, establishing a correct diagnosis before invasive tests and procedures are performed can help prevent unexpected complications.